Tanggung Jawab Penjamin Pada Kredit Macet Dalam Sistem Borgtocht Di Masa Pandemi Covid-19 - Indra Muchlis Adnan; Triyana Syahfitri; Muannif Ridwan (Fakultas Hukum Universitas Islam Indonesia, 2023)
This study discusses the legal responsibilities of guarantors for non-performing loans in the borgtocht system during the Covid-19 Pandemic. The research method used is normative juridical. The research concludes that the guarantor's responsibility for non-permorfing loans in banks under the borgtocht system during the Covid-19 Pandemic era is in accordance with Article 1831 of the Civil Code, namely the guarantor is not required to pay the creditor, unless the debtor is negligent, while the debtor's assets must first be confiscated and auctioned to pay off the debt, but the guarantor cannot ask the creditor to confiscate the goods belonging to the debtor first, before the collateral belonging to the guarantor debtor (borg) is confiscated, if the guarantor releases his privileges through a borgtocht deed, it is regulated in Article 1832 of the Civil Code that the guarantor cannot demand that the debtor’s property be confiscated and sold first to pay off his debt if he has waived his privilege to demand that the borrower's property be confiscated/auctioned first. Settlement efforts in the event of non-performing credit involving the guarantor debtor (borg) during the Covid-19 Pandemic include the debtor has the right to apply for credit restructuring if in fact the debtor has defaulted in making debt payments. Other efforts are by peaceful means such as deliberations or negotiations, so that there is no confiscation of the collateral belonging to the guarantor debtor, and the settlement through legal channels is submitted to the Court to be executed on the guarantee and then auctioned off.Key Words: Responsibility; borgtocht system; Covid-19 AbstrakPenelitian ini membahas tangung jawab hukum penjamin pada kredit macet dalam sistem borgtocht di era Pandemi Covid-19. Metode penelitian ini adalah yuridis normatif. Penelitian ini menyimpulkan bahwa tanggung Jawab penjamin pada kredit macet perbankan dalam sistem borgtocht di era Pandemi Covid-19 sesuai Pasal 1831 KUHPerdata, yaitu penanggung tidak diwajibkan membayar kepada si berpiutang, selain jika si berutang lalai, sedangkan harta si berutang harus terlebih dahulu disita dan dijual untuk melunasi utangnya, namun penjamin tidak dapat memintakan kepada kreditur untuk melakukan penyitaan terhadap barang-barang milik debitur terlebih dahulu, sebelum barang jaminan milik debitur penjamin (borg) disita, apabila penjamin melepas hak istimewanya melalui akta borgtocht, diatur dalam Pasal 1832 KUHPerdata bahwa penanggung tidak dapat menuntut supaya harta pihak peminjam lebih dahulu disita dan dijual untuk melunasi utangnya apabila ia telah melepaskan hak istimewanya untuk menuntut supaya harta pihak peminjam lebih dahulu disita/dijual. Upaya penyelesaian jika terjadi kredit macet yang melibatkan debitur penjamin (borg) di masa Pandemi Covid-19, yaitu debitur mempunyai hak untuk mengajukan restrukturisasi kredit jika memang kenyataannya debitur melakukan wanprestasi dalam melakukan pembayaran utang. Upaya lain dengan cara damai/musyawarah/bernegosiasi, sehingga tidak ada penyitaan agunan milik debitur penjamin, dan penyelesaian dengan jalur hukum diserahkan ke Pengadilan untuk dieksekusi atas jaminan lalu dilelang.Kata-kata Kunci: Tanggung jawab; sistem borgtocht; covid-19